Fucking Our Way to a Better World: An Interview with C. Gallant - Warburton, Rachel (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
In this interview, C. Gallant, manager of Good for Her (gfh), a feminist sex shop in Toronto, discusses her experiences facilitating various workshops offered at gfh and addresses the political dimensions of female sexual pleasure, the whore stigma, colonization of the female body, and feminist workshop pedagogy.